2020
DOI: 10.1101/2020.03.15.992321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formation of uniform reaction volumes using concentric amphiphilic microparticles

Abstract: Reactions performed in uniform microscale volumes have enabled numerous applications in the analysis of rare entities (e.g. cells and molecules), however, sophisticated instruments are usually required to form large numbers of uniform compartments. Here, uniform aqueous droplets are formed by simply mixing microscale multi-material particles, consisting of concentric hydrophobic outer and hydrophilic inner layers, with oil and water. The particles are manufactured in batch using a 3D printed device to co-flow … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…This manufacturing cycle is automated using LabVIEW to fabricate large batches of particles. We also confirm the reproducibility of particle shape across a population of the particles (28). After fabrication, all particles are collected in a 50-ml centrifuge tube and rinsed with a volume of ethanol more than 1000 times the sample volume to eliminate the effect of noncross-linked reagents.…”
Section: Optical Transient Liquid Moldingsupporting
confidence: 61%
See 1 more Smart Citation
“…This manufacturing cycle is automated using LabVIEW to fabricate large batches of particles. We also confirm the reproducibility of particle shape across a population of the particles (28). After fabrication, all particles are collected in a 50-ml centrifuge tube and rinsed with a volume of ethanol more than 1000 times the sample volume to eliminate the effect of noncross-linked reagents.…”
Section: Optical Transient Liquid Moldingsupporting
confidence: 61%
“…These users can then perform assays using monodisperse nanoliter-scale drops through simple shaking and agitation using widely available laboratory equipment. A number of emerging approaches to fabricate shaped microparticles could also be applied to functionalize DCPs ( 26 , 27 ) and scale their size to be compatible with analysis by flow cytometers ( 28 , 29 ). We expect that a number of assays previously demonstrated using lab-on-a-chip infrastructure could be implemented in this “lab-on-a-particle” format in the future, providing greater access to the deployment of powerful biological assays.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogel particles are utilized here both as a solid support to immobilize protein molecules, and as a template for emulsification around the hydrogel matrix. Previously, we and others have shown that spherical particles 31,32 or particles with tailored surface chemistry 33,34 can be used to template drop formation to perform measurements of DNA and protein biomarkers. In this work, we performed digital counting of β-gal enzyme on spherical polyethylene glycol (PEG) hydrogel particles templating drops of ~20 pL volume and achieved femtomolar detection limit.…”
Section: Introductionmentioning
confidence: 99%
“…The latter labelling technique necessitates containment of the fluorescent product and hence has found most utility in dropletbased or oil-encapsulated systems, where the soluble fluorescent product can be contained for sufficient signal generation and multiplexing. [27][28][29][30][31][32] Thus, a limited amount of substrate is accessible for the reaction. Moreover, specialized equipment such as fluorescent microscopes, fluorescent plate readers or fluorescent scanners are necessary to detect the fluorescent signal.…”
mentioning
confidence: 99%
“…Moreover, specialized equipment such as fluorescent microscopes, fluorescent plate readers or fluorescent scanners are necessary to detect the fluorescent signal. 19,24,29,32 Efforts to develop a colorimetric readout for hydrogels have used gold nanoparticle labelling combined with dark-field microscopy. While the sensitivity of this method was comparable to fluorescent labelling, it still requires the use of a microscope for detection using dark-field imaging.…”
mentioning
confidence: 99%